PutA Is Required for Virulence and Regulated by PruR in Pseudomonas aeruginosa - Zheng, Ruiping; Feng, Xuemei; Wei, Xueying; Pan, Xiaolei; Liu, Chang; Song, Ruopu; Jin, Yongxin; Bai, Fang; Jin, Shouguang; Wu, Weihui; Cheng, Zhihui (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa, a Gram-negative opportunistic pathogenic bacterium, causes acute and chronic infections. Upon entering the host, P. aeruginosa alters global gene expression to adapt to host environment and avoid clearance by the host immune system. Proline utilization A (PutA) is a bifunctional enzyme, which converts proline to glutamate. Here we report that PutA was required for the virulence of P. aeruginosa in a murine acute pneumonia model. A putA mutant was more susceptible to oxidative stress compared to the wild type strain. An AraC/XylS family protein, PruR, directly bound to the upstream of -35 box in the putA promoter and activated putA expression. High concentration of proline in bacteria up-regulated pruR expression, which led to the activation of putA expression. As a feedback regulation, glutamate produced by PutA released PruR from the putA promoter and turned off the putA expression. PruR affected bacterial virulence through the regulation of the putA expression. Altogether, these data are the first to reveal that PutA plays an important role in the pathogenesis of P. aeruginosa, as well as to describe the genetic regulation of PutA in P. aeruginosa.